Influence of the NaIO4 Concentration on the Gelation and the Adhesive Strength of Pyrocatechol/Pyrogallol Containing Gelatin Hydrogels - Back, Florence; Ball, Vincent; Arntz, Youri (Frontiers in Materials, 2021)
The presence of catechol groups in hydrogels, either grafted to the constituting polymers or added in the gel formulation allow to increase the adhesion strength of such hydrogels. In this investigation, we add pyrocatechol (1,2-benzenediol) and pyrogallol (1,2,3-benzenetriol) in gelatin solution to form hydrogels using sodium periodate as an oxidant with the aim to induce interactions between pyrocatechol/pyrogallol and the gelatin chains. The gelation kinetics of the hydrogels as well as their adhesion strength and toughness are evaluated as a function of the concentration in NaIO4 for a constant concentration-10 mM- in pyrocatechol/pyrogallol. It came out that the addition of pyrogallol to gelatin (10% w/v) did not improve the adhesion strength on stainless steel when compared to a pristine gelatin gel. As an interesting finding, the addition of pyrocatechol to gelatin allowed for a major improvement of the adhesive strength between two stainless steel plates and allowed to stabilize the gel up to 50° C. However, the pyrogallol modified gelatin gels displayed no thermal stabilization compared to pristine gelatin. The major differences between pyrocatechol and pyrogallol modified gels are explained on the basis of the electrophilicity of the oxidized polyphenols. In addition, the self-healing behavior of the gelatin based gels was investigated as a function of their composition.